Impact of firm specific factors on capital structure: evidence from listedcompanies in colombo stock exchange of sri lanka - Sentheeran, K.; Anandasayanan, S. (University of Jaffna, 2019)
Capital structure is one of the most controversial topics in the world of corporate finance. This study attempts to identify the factors affecting the capital structure and to what extent they impact on the capital structure. To analyze this, the researchers selected a sample of 100 listed companies in CSE for 6 years from 2013 to 2018 using stratified random sampling technique. The determinants of leverage represented by the variables namely Profitability, Tangibility, Size, Liquidity and Sales Growth Rate were independent variables. In addition, Total Debt to Total Assets was employed as dependent variable. The study was analyzed using the statistical tools Descriptive Statistics, Correlation Analysis, Pooled Ordinary Least Square Regression, Fixed Effect and Random Effect. The findings reflected Profitability and Liquidity have significant negative impact on leverage at the same time Tangibility, Firm Size, Sales Growth Rate have significant positive impact on leverage.
Keywords: Capital structure; Profitability; Tangibility; Size; Liquidity; Sales Growth Rate